Evaluating the Efficacy of Aloe Vera Gel Versus 5% Amlexanox Oral Paste in Treating Minor Recurrent Aphthous Ulcers: A Randomized Clinical Study - Sourav Kumar Pradhan; Upasana Sethi Ahuja; Ravi Anjan; Jayanti Bishal; Sachin Mehar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Recurrent aphthous stomatitis/ulceration (RAS) remains one of the most common inflammatory ulcerative conditions affecting the oral mucosa, yet its etiology is still not fully understood. Various systemic and local factors have been proposed as potential contributors to RAS, but due to its complex origins, no definitive treatment exists. Current therapeutic approaches primarily aim to improve the quality of life by alleviating symptoms, speeding up healing, and preventing the recurrence of ulcers. Based on this framework, a study was designed to evaluate and compare the efficacy of Amlexanox oral paste and Aloe vera gel in managing mild RAS. The study enrolled 50 patients with mild recurrent aphthous ulcers, randomly divided into two groups: Group A (Aloe vera gel, 25 patients) and Group B (Amlexanox oral paste, 25 patients). Baseline measurements of erythema, pain, and ulcer size were recorded on the first visit, with follow-up assessments conducted on days three and seven to evaluate changes in ulcer size, pain, and erythema. Additionally, the rate of ulcer recurrence was monitored monthly over six months. The results revealed significant improvements in ulcer size, pain, and erythema in both groups from baseline to day three, baseline to day seven, and from day three to day seven. Both treatment options demonstrated efficacy in reducing ulcer size, pain, and erythema, with Aloe vera gel showing promise due to its unique properties in managing various oral conditions. The study concluded that both Aloe vera and Amlexanox were effective in treating recurrent aphthous stomatitis (RAS), significantly reducing ulcer size, pain, and erythema.